Improved version of the red fluorescent protein (drFP583/DsRed/RFP): research report - Knop, Michael (BioTechniques, 2002)
GFP has established itself as a highly useful tool throughout many areas of modern biology. Recently, the novel fluorescent protein drFP583, also termed DsRed or RFP, was clonedfrom a coral of the Discosoma genus. The protein is only weakly homologous to GFP and has a red emission spectrum, which makes drFP583 an attractive candidate for in vivo double labeling together with GFP variants. However, wildtype drFP583 has several drawbacks, including inefficient folding of the protein, extremely slow maturation of the chromophore, and tetramerization even in dilute solutions. Here we report on important improvements to this reporter that lead to higher levels of fluorescent drFP583 species in the cell. We further characterized our best mutant for applications in yeast and mammalian cell biology.